Especialização de linguagens orientadas a aspectos baseada em extensibilidade de gramáticas - Leonardo Vieira dos Santos Reis (2010)
The development of computational resources and the rise of software industry brought the need to produce software more quickly and with higher complexity. With the increase on program size and complexity, severe problems of maintenance arise, because errors are more dificult to find and correct. So, it is important to create tools that make maintenance easier and improve the productivity of programmers. Domain-SpecificLanguages and Aspect-Oriented Programming can be combined to achieve these goals, building domain-specific aspect-oriented languages as extensions of languages such as AspectJ or AspectC. But building such extensions and embedding them on generalpurpose aspect languages is not an easy task.This work presents XAJ, an aspect-oriented extensible language based on AspectJ. XAJ provides features to build extensions and embedded domain-specific aspect-oriented languages. XAJ has a new compilation unit called syntax class, whichen capsulates the whole denition of a language extension, improving modularity and portability of extensions. Mechanisms for symbol import allow the definition of newgrammar rules with local scope. Extensions in XAJ are portable because they are completely defined with the language itself, without the need of additional tools for the implementation.